Effect of pre-mix pendimethalin + pyrazosulfuron on grain yield and yield attributes of rice (Oryza sativa L.) - Kaur, Tarundeep; Bhullar, Makhan Singh; Sekhon, Fatehjeet Singh (Journal of Cereal Research, 2019)
The experiment was carried out at Research Farm in Department of Agronomy, Punjab Agricultural University, Ludhiana to work out effective weed management strategy in transplanted rice. Nine treatments viz. pendimethalin + pyrazosulfuronat 675 + 15 g, 900 + 20 g, 1125 + 25 g, pendimethalin at 1500 g, pyrazosulfuronat 15 g, pyrazosulfuronat 20 g, metsulfuron + chlorimuronat 4 g ha-1, hand weeding and weedy check replicated thrice laid out in randomized complete block design (RCBD). The results revealed that pendimethalin + pyrazosulfuron at 1125 + 25 g ha-1, provided effective weed control (73.8-86.2% weed control efficiency) over other treatments. During 2015, pendimethalin + pyrazosulfuron at 1125 + 25 g ha-1 was found profitable with higher rice grain yield (6.65 t ha-1) and cost benefit ratio (1:2.25). Pendimethalin + pyrazosulfuronatat 900 + 20 g ha-1, was found profitable with higher rice grain yield (7.35 t ha-1) and cost benefit ratio (1:2.50) and was statistically at par with pendimethalin + pyrazosulfuron at 1125 + 25 g ha-1 for weed control during 2016.DOI:http://doi.org/10.25174/2249-4065/2019/95896